A Hybridized Local and Charge‐Transfer Excited State for Highly Efficient Fluorescent OLEDs: Molecular Design, Spectral Character, and Full Exciton Utilization. Issue 9 (27th June 2014) - Li, Weijun; Pan, Yuyu; Yao, Liang; Liu, Haichao; Zhang, Shitong; Wang, Chu; Shen, Fangzhong; Lu, Ping; Yang, Bing; Ma, Yuguang
<x xml:space="preserve">Abstract</x> For a donor–acceptor (D–A) molecule, there are three possible cases for its low‐lying excited state (S1): a π–π* state (a localized electronic state), a charge‐transfer (CT) state (a delocalized electronic state), and a mixed or hybridized state of π–π* and CT (named here as the hybridized local and charge transfer (HLCT) state). The HLCT state is an important excited state for the design of next‐generation organic light‐emitting diode (OLED) materials with both high photoluminescence (PL) efficiency and a large fraction of singlet exciton generation in electroluminescence (EL). According to the principle of state mixing in quantum chemistry, a series of twisting D–A molecules are designed and synthesized, and their HLCT state characters are verified by both fluorescent solvatochromic experiments and quantum chemical calculations. The CT components in the HLCT state, which greatly affect the molecular optical properties, are found to be enhanced with a decrease of the twist angle of the D–A segment or an increase of the D–A intensity in these twisting D–A molecules. In OLEDs, using these HLCT compounds as the emitting layer, the maximum exciton utilization efficiency is harvested up to 93%. Surprisingly, an exception of Kasha's rule is revealed in some HLCT compounds: restricted internal‐conversion (IC) from the high‐lying triplet state (T2) to the low‐lying triplet T1, and a reopened path of reverse intersystem crossing (RISC) from T2 to S1 or S2, based on the analysis of the excited‐state energy levels and the measurement of the low‐temperature spectrum. RISC from T2 to S1 (S2) as a "hot exciton" channel is believed to contribute to the large proportion of the radiative singlet excitons.